A Via Pulchritudinis, e a nova evangelização na América Latina - Santoro, Filippo (Revista Eclesiástica Brasileira, 2006)
Dom Filippo Santoro, Bispo de Petrópolis, RJ, mostra a fecundidade da via pulchritudinis em teologia (o caminho para Deus através da Beleza) e sua relevância para a tarefa da nova evangelização na América Latina. Repassa o que diz a Escritura sobre o tema, lembra a teologia da beleza em H.U. Von Balthasar e no magistério de Paulo VI e João Paulo II para, na parte final do estudo, sugerir respostas aos desafios à nova evangelização na América Latina e, especificamente, no Brasil. “É indispensável – diz Dom Filippo – que o anúncio de Cristo, Beleza feita carne, seja uma proposta existencial na qual se possa perceber a possibilidade da realização integral da vida”. Abstract: Don Filippo Santoro, Bishop of Petrópolis, State of Rio de Janeiro, demonstrates the fecundity of the pulchritudinous way (the road to God through Beauty) in Theology and its relevance for the task of the new evangelization in Latin America. Reviewing what the Holy Scripture says about the subject, he reminds us of the Theology of Beauty in H.U. Von Balthasar and in the teachings of both Paul the 6th and John Paul the 2nd. In the final part of the study, the author proposes some answers for the challenges faced by the new evangelization in Latin America and specifically in Brazil. “It is paramount”– says Don Filippo –“that Christ’s announcement, Beauty made flesh, be an existential proposition in which we may perceive the possibility of a fully realized life.